Islam dan kerukunan umat beragama: Merajut kemanusiaan universal - Mahmud, Adnan (MAN 4 Kota Pekanbaru, 2025)
Religious pluralism is an undeniable reality in contemporary society, yet much of the discourse on Islamic tolerance remains limited to normative-theological or historical approaches, often overlooking Islam’s practical role in fostering interreligious harmony and addressing global challenges. This study aims to analyze the concept and practice of interreligious harmony from an Islamic perspective and explore Islam’s contribution to universal humanity. Using a library research method, the study collects and critically analyzes various classical and contemporary sources, including tafsir literature, scholarly books, and academic articles, to construct a comprehensive theoretical framework. The findings reveal that Islam offers a strong theological foundation for interfaith coexistence, exemplified through the principles of rahmatan lil ‘ālamīn, lakum dīnukum wa liya dīn, and reinterpretations of ahl al-dzimmah. Moreover, Islam contributes to global humanity through the promotion of ukhuwah insāniyah, social justice, environmental ethics, and peacebuilding values. These universal Islamic values, when actualized, have the potential to foster multicultural education, inclusive public policies, and sustained interreligious dialogue. Therefore, this study positions Islam not only as a religion of private devotion but also as a transformative force capable of building a more peaceful, just, and sustainable global civilization.